Comfort Value Of Kartika Sukabumi Hospital Lobby - Veronica, Lilian; Susetyarto B, Susetyarto B; Puspatarini, R.A, Puspatarini, R.A (Devotion : Journal of Research and Community Service, 2024)
The comfort of the hospital lobby is very influential in ensuring that health services in the hospital run optimally. Comfortable lobby conditions can reduce anxiety when patients have to wait their turn to be examined or wait for medicine from the pharmacy. Apart from that, the comfortable lobby creates optimism for recovery for patients and their families, including medical personnel who work at the hospital. This research aims to measure how significant the influence of room comfort, thermal comfort, visual comfort and audio comfort is on the comfort of the lobby room seen from the architectural design of the room. The benefits of the research enrich the results of previous research that building comfort variables influence the dynamics of perceptions of physical comfort. The research uses quantitative methods and data collection techniques are carried out by direct observation and questionnaires that are distributed to hospital visitors, managers, medical teams and patients. Data were analyzed using descriptive quantitative methods to assess the comfort level of the hospital lobby. From the results of this research, it is concluded that the aspect of freedom of movement has the greatest influence on the comfort level of the lobby space, so it must be taken into consideration when designing a hospital lobby that is comfortable for visitors.